Current status and challenges of CAR-T cell therapy in the treatment of haematological cancer - Yu Mengqi (BIO Web of Conferences)
Chimeric Antigen Receptor T (CAR-T) cell therapy is a promising cellular immunotherapy that involves the use of genetically modified T cells to target and combat hematological malignancies. This approach has shown significant effectiveness and has emerged as a key area of interest in oncological treatment. Despite its potential, the path to broader application is fraught with challenges including cytokine release syndrome (CRS), immune effector cell-associated neurotoxicity syndrome (ICANS), drug-resistant relapses, side effects, and the high costs associated with manufacturing. These issues have constrained the wider adoption of CAR-T cell therapy. This paper outlines key advancements in the clinical trials of CAR-T cell therapy within the scope of hematological oncology and identifies the primary challenges encountered. The objective of this study is to provide insights that may inform the development of future CAR-T therapies for hematological tumors.